PENGARUH PEMBELAJARAN DENGAN PENDEKATAN ETNOMATEMATIKA TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS IV SEKOLAH DASAR: Penelitian Kuantitatif - Regina Nanda Winata; Muhammad Fendrik; Eva Astuti Mulyani (STKIP Subang, 2025)
This study aims to determine the effect of learning using an ethnomathematics approach on the mathematical understanding ability of fourth-grade elementary school students. This research is a quantitative experimental study employing a Quasi-Experimental Design with a Nonequivalent Control Group Design. The subjects consisted of class IV.A as the experimental group and IV.B as the control group. A pretest was administered before the treatment, and a posttest was conducted after the treatment. Based on the hypothesis test using the Mann-Whitney U test, the obtained Asymp. Sig. (2-tailed) value was < 0.001 < 0.05, indicating that H0 is rejected and Ha is accepted. This result is supported by the coefficient of determination test, which showed an R Square value of 0.6112 or 37%. Therefore, it can be concluded that learning using an ethnomathematics approach has an effect on the mathematical understanding ability of fourth-grade elementary school students.